2019
DOI: 10.1088/1361-665x/ab4d5d
|View full text |Cite
|
Sign up to set email alerts
|

A traveling-wave ultrasonic motor utilizing a ring-shaped alumina/PZT vibrator

Abstract: Considering that high Young's moduli and low ultrasonic attenuation of fine ceramics may enhance driving force and reduce energy dissipation, in this study, we exploit the usage of fine ceramics as vibrating bodies of ultrasonic motors. Several alumina vibrating bodies were fabricated and bonded to annular lead-zirconate-titanate (PZT) disks to form ring-shaped vibrators, where traveling waves with the 3rd bending modes were excited to frictionally drive the rotor. First, we explored the fundamental vibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Mechanical performances showed that the motor can obtain rotary speed of 350 r/min and the maximum torque is 186 N•mm under the voltage of 300 Vp − p. Wu et al, fabricated & investigated a ring-shaped alumina/PZT vibrator to form a traveling-wave USM. The rotation speed of the alumina/PZT motor was larger than that of the stainlesssteel/PZT motor, meanwhile, it exhibited superior maximal-torque-to-voltage and maximal-output-power-to voltage ratios [102].…”
Section: Multivibratorsmentioning
confidence: 96%
“…Mechanical performances showed that the motor can obtain rotary speed of 350 r/min and the maximum torque is 186 N•mm under the voltage of 300 Vp − p. Wu et al, fabricated & investigated a ring-shaped alumina/PZT vibrator to form a traveling-wave USM. The rotation speed of the alumina/PZT motor was larger than that of the stainlesssteel/PZT motor, meanwhile, it exhibited superior maximal-torque-to-voltage and maximal-output-power-to voltage ratios [102].…”
Section: Multivibratorsmentioning
confidence: 96%
“…The output power and efficiency corresponding to 360 N were higher than those to 240 and 480 N probably because the frictional loss was smaller [40,41]. Most TW motors cannot provide high efficiencies as the vibration velocities differ among the driving feet [21,31,35]. In contrast, only one wave crest exists on each vibrating body; this may suppress vibrationvelocity-difference-induced frictional loss and consequently enhance the efficiency.…”
Section: A Load Characteristicsmentioning
confidence: 98%
“…Besides, the calculated value of keff is ~30% (see Section II), in good agreement with the experimental results. Subsequently, the vibration velocity distribution was investigated via interferometric measurement [35]. The voltages were applied with power amplifiers (HSA4051, NF Corporation, Yokohama, Japan).…”
Section: Vibration Propertiesmentioning
confidence: 99%
“…In contrast, the transducers of lowquality factor have lower frequency and longer wavelength with higher penetration power. They also have broad-band [25]. Q depends on the operating frequency, f 0 and the bandwidth, BW [20] as follow:…”
Section: Quality Factor Analysismentioning
confidence: 99%